Combined Odontoid (C2) and Atlas (C1) Fractures in Geriatric Patients: A Systematic Review and Treatment Recommendation - Spiegl, Ulrich J.A.; Keil, Holger; Krause, Julia; Osterhoff, Georg; Scheyerer, Max J.; Schnake, Klaus John; Perl, Mario (Global Spine Journal, 2023)
Study Design: Systematic review. Objective: The aim of this study was to conduct a systematic overview of the pathogenesis and the treatment options of combined odontoid and atlas fractures in geriatric patients. Methods: This review is based on articles retrieved by a systematic search in the PubMed and Web of Science databases for articles published until February 2021 dealing with combination fractures of C1 and C2 in geriatric patients. Results: Altogether, 438 articles were retrieved from the literature search. A total of 430 articles were excluded. The remaining eight original articles were included in this systematic review depicting the topics pathogenesis, non-operative treatment, posterior approach, and anterior approach. The overall level of evidence of the studies is low. Conclusion: Combined odontoid and atlas fractures in the geriatric population are commonly caused by simple falls and seem to be associated with atlanto-odontoid osteoarthritis. Non-operative treatment with a cervical orthosis is a feasible treatment option in the majority of patients with stable C2 fractures. In case of surgery posterior C1 and C 2 stabilization and anterior triple or quadruple screw fixation are possible techniques. Some patients may also deserve an occipito-cervical fusion. A possible treatment algorithm is proposed.
CRIS-Team Scopus Importer:2023-05-05